A ten-year risk of developing diabetes mellitus in health personnel - Martínez González, Janeth; Galicia Rodríguez, Liliana; Villarreal Ríos, Enrique; Guerreo Mancera, Mariana del Rayo; Franco Saldaña, Mireya; Aparicio Solís, Laura Sofía (Universidad y Salud, 2024)
Introduction: In Mexico, the prevalence of type 2 diabetes mellitus is 10.2%. Objective: To determine the 10-year risk of developing diabetes mellitus in health personnel from a primary care institution. Materials and methods: A transversal descriptive study on primary care health personnel. The 10-year risk of developing diabetes was assessed through the FINDRISC instrument, which takes into account eight dimensions, each having a specific score to generate five risk categories. The statistical analysis included percentages, averages, and confidence intervals for both percentages and averages. The risk of diabetes at 10 years was identified for the general population, according to their job positions and gender. Results: The study demonstrated that the 10-year risk of developing diabetes was low (22.1%; 95% CI 35.4-48.0), mild (20.9 %; 95 % CI 15.7-26.1), high (13.2 %; 95 % IC 8.9-17.5), and very high (2.1 %; 95% CI 0.3-3.9). Conclusion: There is a slightly elevated 10-year risk of developing diabetes mellitus in the health personnel from the studied medical unit.